Meaning and gender differences - Bezalel, Jonathan; Mugerman, Yevgeny; Winter, Eyal (Journal of behavioral and experimental economics, 2021)
•We test gender differences with regards to the perceived meaning (of donations).•We show that women's perceived meaning is more sensitive to the existence of gift rewards than that of men.•When the gift incentive is nonexistent, women attribute a greater sense of meaning to their contribution, whereas this effect is largely absent or even reversed in men.•We conjecture that women are more “Kantians” than men in their attitude towards decisions involving intrinsic motivation. This study utilizes the crowdfunding setting, and examines gender differences with regard to the perceived meaning of donations. The crowdfunding mechanism creates a singular reciprocal interaction where motivations can be examined and compared. We show that women's perceived meaning is more sensitive to the existence of gift rewards than that of men. When the gift incentive is nonexistent, women attribute a greater sense of meaning to their contribution, whereas this effect is largely absent or even reversed in men. Our findings have far-reaching implications in all aspects of donor retention strategies. Specifically, our findings indicate that women are more aligned with the Kantian doctrine of rejecting self-interest considerations of altruistic behavior than men.